STUDI PERSEPSI MASYARAKAT KRISTEN: Perbedaan Pandang Gereja-Gereja Jabotabek Atas Roh Kudus: CHRISTIAN COMMUNITY PERCEPTION STUDY: Differences in View of the Jabotabek Churches over the Holy Spirit - Robby Chandra; Elia Tambunan (Sekolah Tinggi Teologi Satyabhakti, Malang)
This is a preliminary study to explore the relationship between the church denomination background with their members’ perception of the Holy Spirit’s role, the function of baptism in the Spirit, and the locus of the Holy Spirit’s presence as how they percepted. Respondents were chosen based on cluster and availability in quantitative research approach. Before, it is hypothesized that subjects’ denominational background as the independent variable correlates positively with their view of the Holy Spirit role, the function of Baptism in the Spirit, and their understanding about the presence of the Holy Spirit today. By using Pearson correlation test, it is found that no strong correlation between the subjects’ denomination background with their view of the roles of the Holy Spirit, the function of Baptism in the Spirit, and the locus of the Holy Spirit’s presence. Various possibilities were discussed to shed light of the phenomenon primarily in relation to the statements of many theologians that Western or some of Eastern churches tend to neglect holistic experience and theological concepts of the Spirit. The scientific contribution of this paper is to include the study of Christian perceptions as a field of study in practical theology, and also in Pentecostalism which has not been much in the Indonesian context. === Ini adalah studi pendahuluan untuk mengeksplorasi hubungan antara latar belakang denominasi gereja dengan persepsi anggotanya tentang peran Roh Kudus, fungsi baptisan dalam Roh, dan lokus kehadiran Roh Kudus sebagaimana persepsi mereka. Responden dipilih berdasarkan cluster dan ketersediaan dalam pendekatan penelitian kuantitatif. Sebelumnya, dihipotesiskan bahwa latar belakang kelompok keagamaan sebagai variabel independen berkorelasi positif dengan pandangan mereka tentang peran Roh Kudus, fungsi Baptisan dalam Roh, dan pemahaman mereka tentang kehadiran Roh Kudus dewasa ini. Dengan menggunakan uji korelasi Pearson, ditemukan bahwa tidak ada korelasi yang kuat antara latar belakang denominasi subyek dengan pandangan mereka tentang peran Roh Kudus, fungsi Baptisan dalam Roh, dan tempat kehadiran Roh Kudus. Berbagai kemungkinan dibahas untuk menjelaskan fenomena ini terutama sehubungan dengan pernyataan banyak teolog bahwa gereja-gereja Barat atau Timur cenderung mengabaikan pengalaman holistik dan konsep-konsep teologis Roh. Sumbangan ilmiah dari tulisan ini ialah memasukkan studi persepsi masyakat Kristen sebagai satu bidang kajian dalam teologi praktika, dan juga dalam Pentakostalisme yang belom banyak dalam konteks Indonesia.